(untitled) (Asian Journal of Medical Sciences, 2024)
Abdominoscrotal hydrocele (ASH) is a relatively rare variant of hydrocele in both adult and pediatric populations. The incidence among adults is <1% of other types of hydroceles, which are different from most cases related to persistent processus vaginalis. It presents as a dumbbell-shaped cystic collection with cross-fluctuation in the abdominoscrotal region and the inguinal canal acting as the rod connecting two masses. The abdominal swelling could be retroperitoneal or intraperitoneal. Clinical examination can lead to a suspected diagnosis of ASH, but confirmation relies on ultrasonography and computed tomography. Spontaneous resolution of ASH has been unlikely, and hence surgical intervention is recommended. In this study, we present three cases with ASH who underwent surgical repair using different methods.